Problem of Vizualizing Semantic Layer of a Large Number of Topics in Topic Maps - Dudycz, Helena (Advanced Information Technologies for Management – AITM 2009, 2009)
In the last few years an increasing interest of visualization's applications to the presentation of business information has occurred. Visualization should support the user in finding relevant information. One of the solutions which can help managerial staff to obtain essential information is that of a topic map. This is the standard uniform introduced by the International Organization for Standardization used to describe knowledge structures and associate them with information resources. Topic map is the visualization concept which can support exploration of large data sets. The advantage of visual data exploration is that the user is directly involved in the data mining process. Purpose of this article is to solve problem of large number of topics in usage topic map as a tool enabling visual exploration of huge, complex and multidimensional data set. Relating to that in the first part standard of topic map was characterized and possibilities of the use of a topic map for creation application enabling visual exploration of data were pointed out. The next part describes the solutions of the problem of a large number of topics.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 66-76